On Materiality and Meaning: Ethnographic Engagements with Reuse, Repair & Care. Issue 1 (25th January 2019) - Isenhour, Cindy; Reno, Joshua
The reimagination and revaluation of discarded goods, through repair and reuse is, for many, a quotidian and mundane element of everyday life. These practices are the historical precedent and continue to be the stuff of common sense for a significant portion of human society. And yet, reuse, repair and other elements of a 'circular economy' have recently emerged as a significant focus in environmental and economic policy. Proponents claim that reuse practices represent a potentially radical alternative to mainstream consumer culture and a form of carework that generates new social possibilities and personal affects. This essay explores the myriad dimensions of reuse as care, relational practice and as consumer alternative by examining these practices in their social context, lived experience and as embedded within larger political and economic structures of capitalist accumulation and abandonment. We argue that the study of reuse, in old and new forms, takes on added political significance in an era of environmental and economic crises, especially as a critical part of state-based approaches toward the circular economy that attempt to appropriate carework in new forms of value generation.